W. Selden Gale et al., Revised Ordinances of the City of Galesburg 69 (1896) - (:unkn) unknown (My University, 1869)
§ 1: Prohibited the sale or keeping for sale of gunpowder without a license. Licenses shall be limited to storing twenty-five pounds of gun powder at any one time unless it is stored in a secure magazine or fire-proof powder house located at least one hundred feet from any occupied building. Violators subject to a fine of twenty dollars.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER